Digital Organizational Support and Employee Well-Being: The Role of Moderating Religious Coping - Mohamad Sodikin; Mudrik; Heru Sulistyo (IJUS | International Journal of Umranic Studies, 2023)
The rapid and unpredictable business environment changes can affect work patterns and organizational sustainability, such as during the Covid-19 pandemic. Organizations are required to carry out social distancing by working from home to provide services to the community. Emotional exhaustion can arise when the work process has to be done at home for a relatively long time with social interactions restrictions. Based on conservation of resources theory, this study examined the effect of working from home via telework on employee well-being for civil servants in the public sector. The study involved 150 civil servants as respondents. Data analysis using structural equation modelling. Results showed that digital organizational support has no significant effect on emotions. Religious coping strategies significantly moderate the relationship between emotional and employee well-being. Besides, emotions do not entirely mediate the relationship between digital organizational support and employee well-being. The findings of this study have important implications for organizations, especially regarding overcoming emotional exhaustion during the Covid-19 pandemic. The research limitations, future research and managerial implications are also discussed in the study.